FLACC 07. - Dander, Patrizia; Van Woensel, Jan; Deprez, Koen; Koeman, Jean Bernard; Mertens, Piet; Oosting, Alien; Peulen, Karin; Rutten, Bart; Vanden Ecker, Jochem; Van Gerrewey, Christophe; Zelck, Francis; FLACC, Genk (Genk : FLACC: Werkplaats voor beeldende kunstenaars, 2008)
de Beer, Sue ; Deprez, Koen ; Goiris, Geert ; Koeman, Jean Bernard ; Kent, Mark ; Oosting, Alien ; Robert, Jimmy ; Vanden Ecker, Jochem ; Wenzel, Anne ; Fritsch, Matthias ; Lorenz, Martin ; Kabasinskaite, Ieva ; et al.
Schenking FLACC
Overzicht werkplaatsen in 2007, FLACC, Genk
kunstcatalogus